Antimicrobial action and phytochemical characterization of Eucalyptus and Pine volatile oils (Research, Society and Development, 2025)
Despite scientific advancements, there has been growing global concern regarding the increasing spread of microorganisms resistant to antibiotics. Objectives: to determine the antimicrobial activity of the essential oils of Pinus sp. and Eucalyptus citriodora against clinically relevant pathogens Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Candida albicans. Methodology: The analysis and phytochemical characterization of the essential oils were performed using Gas Chromatography Mass Spectrometry. The antimicrobial activity was determined using the disk diffusion method according to the guidelines of the Clinical and Laboratory Standards Institute, based on reference microorganisms cataloged in collections provided. The data obtained were analyzed using simple frequency measures and dispersion, and the collected information was recorded, tabulated, and presented in tables and graphs. Results: The main compounds found in the eucalyptus essential oil were (R) citronellal (60.71%), eucalyptol (11.70%), and isopulegol (9.91%), while in the pine essential oil, the main compounds were α-terpineol (28.78%), terpinolene (15.57%), and limonene (10.35%). Regarding antimicrobial activity, the eucalyptus essential oil showed activity against S. aureus, E. coli, and C. albicans, while the pine oil showed activity against all the microorganisms studied. Synergistic action of the essential oils was observed against the fungus C. albicans, with complete inhibition of this microorganism. Conclusion: The essential oils of eucalyptus and pine showed activity against the microorganisms studied, suggesting their potential as ingredients for the development of new products, as well as an alternative antimicrobial agent.